1998
DOI: 10.1007/s004110050119
|View full text |Cite
|
Sign up to set email alerts
|

The Semipalatinsk nuclear test site: a first analysis of solid cancer incidence (selected sites) due to test-related radiation

Abstract: Since 1956, cancer incidences have been analysed in several rayons of the Semipalatinsk oblast, with cross-sectional analyses being conducted every 5 years. Data on different tumor localizations were recorded within a heavily contaminated so-called main area of nine villages (estimated average effective equivalent dose about 2000 mSv) and a so-called control area (estimated average effective equivalent dose about 70 mSv), each including approximately 10000 persons. Up to 1970, the excess cancer incidence in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…As far as the health effects of these explosions are concerned, the archival material available is scanty and incomplete. Epidemiological studies performed on the Kazakhstan population over a 27-year-observation period reported a significant increase of malignant tumours [6]. It is worth noting that the mortality risk from all types of malignant tumours was almost the same for residents in the Semipalatinsk area and A-bomb survivors of Hiroshima and Nagasaki [2].…”
Section: Discussionmentioning
confidence: 99%
“…As far as the health effects of these explosions are concerned, the archival material available is scanty and incomplete. Epidemiological studies performed on the Kazakhstan population over a 27-year-observation period reported a significant increase of malignant tumours [6]. It is worth noting that the mortality risk from all types of malignant tumours was almost the same for residents in the Semipalatinsk area and A-bomb survivors of Hiroshima and Nagasaki [2].…”
Section: Discussionmentioning
confidence: 99%
“…An earlier analysis on the basis of several crosssectional incidence studies that have been carried out every 5 years, revealed a higher cancer incidence in the exposed area compared to the unexposed area [5].…”
Section: Forthcoming Data Analysesmentioning
confidence: 99%
“…In addition, a cross-sectional study on the health status of the population was carried out at 5-year intervals. The results of these cross-sectional studies have been published earlier [13]. The basic data for the cohort study is described in [6].…”
Section: Epidemiologymentioning
confidence: 99%